2020
DOI: 10.3389/fphys.2020.568667
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Kv7 Channels in Neural Plasticity and Behavior

Abstract: Activity-dependent persistent changes in neuronal intrinsic excitability and synaptic strength are widely thought to underlie learning and memory. Voltage-gated KCNQ/K v 7 potassium channels have been of great interest as the potential targets for memory disorders due to the beneficial effects of their antagonists in cognition. Importantly, de novo dominant mutations in their neuronal subunits KCNQ2/K v 7.2 and KCNQ3/K v 7.3 are associated with epilepsy and neurodevelopmental disorder characterized by developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 106 publications
1
27
0
Order By: Relevance
“…At the nucleus, UBE3A has been shown to regulate chromatin structure, DNA methylation and transcriptional regulation [37][38][39][40]. Interestingly, 8 out of the 10 genes found mutated in this study are mainly involved in synapsis (VAMP2, SYNGAP1, SLC6A1 and KCNQ3) [41][42][43][44] and chromatin remodeling or transcription regulation (TBL1XR1, SATB2, SMARCE1 and ASXL3) [45][46][47][48].…”
Section: Resultsmentioning
confidence: 95%
“…At the nucleus, UBE3A has been shown to regulate chromatin structure, DNA methylation and transcriptional regulation [37][38][39][40]. Interestingly, 8 out of the 10 genes found mutated in this study are mainly involved in synapsis (VAMP2, SYNGAP1, SLC6A1 and KCNQ3) [41][42][43][44] and chromatin remodeling or transcription regulation (TBL1XR1, SATB2, SMARCE1 and ASXL3) [45][46][47][48].…”
Section: Resultsmentioning
confidence: 95%
“…Although Kv7 channels have been suspected to be involved in functional plasticity (29), our study provides the first direct evidence for its involvement in activity-dependent intrinsic regulation of intrinsic excitability.…”
Section: Involvement Of Kv7 Channels In Intrinsic Plasticitymentioning
confidence: 73%
“…Additionally, Cabello-Arreola et al [ 66 ] (2020) reported a reduction in the protein coded by KCNQ3 (potassium voltage-gated channel subfamily Q member 3) in suicide victims. This protein serves as a building block for the M-channel, a slow working potassium channel that is involved in the regulation of neuron excitability, which has previously been associated with epilepsy, attention deficit hyperactivity disorder, and psychiatric disorders[ 72 ].…”
Section: Use Of -Omics In Research Into Suicidal Behaviourmentioning
confidence: 99%